2020
DOI: 10.1002/jper.19-0593
|View full text |Cite
|
Sign up to set email alerts
|

Association between periodontitis and systemic medication intake: A case‐control study

Abstract: Background: To investigate the frequency of systemic drugs taken by elderly patients with or without periodontitis and the possible association between medication consumption and the severity of periodontitis. Methods: A total of 1221 patients, including 608 with generalized moderate to severe periodontitis (periodontitis group) and 613 age-and gender-matched individuals with healthy periodontium (healthy group) were selected. Systemic conditions, medications and periodontal status were recorded. Medication in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Patients with moderate or severe periodontitis (probing depth ≥4 to 5 mm) have a significantly higher risk for developing type 2 diabetes after 5 years of follow-up (RR = 2.47; 3.45). [25][26][27][28][29] Fasting blood glucose, HbA1c, and HOMA-IR values were significantly higher in patients with diabetes with severe periodontitis than in patients with diabetes alone. 30 In addition, some clinical trials showed that after nonsurgical periodontal treatment in patients with diabetes, blood glucose levels and HbA1c were significantly decreased concomitant with improved periodontal status, and the required medication dosage for managing diabetes was reduced as well.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Patients with moderate or severe periodontitis (probing depth ≥4 to 5 mm) have a significantly higher risk for developing type 2 diabetes after 5 years of follow-up (RR = 2.47; 3.45). [25][26][27][28][29] Fasting blood glucose, HbA1c, and HOMA-IR values were significantly higher in patients with diabetes with severe periodontitis than in patients with diabetes alone. 30 In addition, some clinical trials showed that after nonsurgical periodontal treatment in patients with diabetes, blood glucose levels and HbA1c were significantly decreased concomitant with improved periodontal status, and the required medication dosage for managing diabetes was reduced as well.…”
Section: Discussionmentioning
confidence: 98%
“…Cross‐sectional and longitudinal studies have shown that periodontitis is a risk factor for diabetes. Patients with moderate or severe periodontitis (probing depth ≥4 to 5 mm) have a significantly higher risk for developing type 2 diabetes after 5 years of follow‐up (RR = 2.47; 3.45) 25–29 . Fasting blood glucose, HbA1c, and HOMA‐IR values were significantly higher in patients with diabetes with severe periodontitis than in patients with diabetes alone 30 .…”
Section: Discussionmentioning
confidence: 99%
“…8,9 It is well-documented that periodontal disease is a complex disease with multiple potential contributing factors. These include genetic 10 and epigenetic influences, 11 medication use 12 and/or environmental factors, 13 which together promote periodontal disease initiation and progression. Low socioeconomic status, poor oral hygiene, and oral health related behaviors, psychological stress, and/or depression, increased age, ethnicity, diet/obesity, and systemic health comorbidities are risk factors that contribute to the prevalence of periodontal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, this study only assessed the presence of hypertension without recording the data on medication, thus the association can not be ruled out from the influence of medication side effects. Besides that, the current literature remains inconclusive regarding the effect of medications, as with no or positive associations are reported conclusively [25]. Such as, thiazide-like diuretic, which is one of the first line antihypertensive therapies, contributes to the development of periodontal disease [26] by reduced salivary rate and composition [27].…”
Section: Discussionmentioning
confidence: 99%